RELATIONSHIP OF PB LEVELS WITH BLOOD PRESSURE IN TIRE REPAIRMAN ON PANTURA HIGHWAY, PEKALONGAN CITY - Tri Minarsih (Jurnal Farmasi Sains dan Praktis, 2021)
Lead (Pb) is a type of metal that has an acute effect on blood pressure and causes hypertension if it accumulates in the blood for a long time. Many types of work are at risk to cause accumulation of Pb in the blood. One of the work sectors that is estimated to be potentially contaminated by Pb is the tire repairman that exists along the highway, which comes from paint, dust (residual fuel) engines and others. The purpose of this study was to determine the relationship between Pb levels and blood pressure in tire repairman on Pantura Highway, Pekalongan City. This type of research is Analytic Observational. The sample used in this study was the tire repairman on Pantura Highway, Pekalongan City, who were willing to be a respondent of 13 people. The research data were taken from blood samples of tire repairman to measure their Pb levels, measure blood pressure and questionnaires. The results of this study are the Pb levels in the blood of tire repairman on Pekalongan City's Pantura Highway, all exceeding normal with the lowest value of 19,76 (µg / dL) and the highest of 32,55 (µg / dL). The average systolic blood pressure obtained at the tire repairman was 149.61mm Hg, while the diastolic blood pressure was an average of 92,46 mm Hg In conclusion, the value of R obtained was 0,09995 for the correlation of Pb content with systole and 0,1551 for the correlation of Pb levels with diastole. This shows a correlation that is not so strong 9,99% (the contribution of Pb levels to the system) and 15,51% (the contribution of Pb levels to diastole).